Art and Culture in Nineteenth-Century Russia - Stavrou, Theofanis George (Indiana University Press, 1983)
In terms of cultural achievements, the nineteenth century was Russia's golden age, when increased literacy and heightened national consciousness combined to spur the growth of high culture. This rich collection of thirteen original essays by leading scholars delves into the relationship of Russian culture to society, circa 1775-1885.